Eco Bridges: a Sustainable Strategy for Biodiversity: An inclusive development - Gómez Macias, Mariana; Vera Guarnizo, María Claudia; Montaño Cabrera, Yeimy Gisela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The importance of implementing ecological bridges in the Andean region of Colombia is increasing, it is enough to review the numerous deaths of animals on the roads and realize that many of them are animals in danger of extinction. The objective of this research is to demonstrate the great need to implement ecological bridges on the Girardot-Melgar road. Therefore, in the present investigation, the road from Girardot-Cundinamarca Km 8+000 to Melgar-Tolima Km 24+000 was analyzed, where an analysis of the animals that are run over on the roads was carried out, evaluating the feasibility of implementing ecological bridges.